Radioprotección en radioyodoterapia para cáncer tiroideo - Carmona C., Jaime; Zhindon P., Juan Pablo; González A., Javiera; Fernández B., René; González E., Patricio (Revista Hospital Clínico Universidad de Chile, 2014)
Radioiodine therapy is a widely useful tool used in adjuvant treatment for differentiated thyroid cancer and has proven beneficial effect. Is crucial to safeguard and prevent caregivers, medical staff and the general public from the patients treated with I-131 in order to minimize radiation exposure and avoid unnecessary irradiation. There are many guidelines recomendations (ATA, EANM) that are helpful for the prevention, minimize of exposure and possible contamination from the patient. The aim of this study is to provide radiation protection measures used in radioiodine therapy order to avoid contamination of the patient and his environment.